(untitled) (Transport systems and technologies, 2021)
The article deals with the issues of a conceptual approach to determining the life cycle of a passenger car. The fleet of passenger car mainly consists of models developed and manufactured in the 70-90s of the last century at car plants in Germany and Russia. They are obsolete both morally and physically. This necessitates the renewal of the passenger car fleet by purchasing cars of both domestic and foreign production. In modern conditions, the user of new technology is interested not only in the purchase price, but also in the after-sales costs. This is reflected in the life cycle cost. It is proposed to use a cascade life cycle model for a passenger car. The stages of the life cycle of a passenger car during operation on the railways of Ukraine have been determined. The components of each stage of the life cycle of a passenger car are considered. For a transport company that intends to operate a passenger car, the costs of the first three stages are directly expressed in the initial cost of the car - the purchase price. The life cycle cost (LCC) of a passenger car will be determined by summing up the individual outflow of funds (expenses) at each specific stage (calculation step) of the service life of the equipment. The life cycle assessment of the technical system of railway transport can work at any stage of the life cycle.